La arquitectura como medio de empoderamiento cívico - Maccaglia, Marta (2023)
In Peru there are 48 native languages, 11 ecological regions, 84 of the 117 different «life zones» in the world. Can architects operate from an active and participatory action with respect that strengthens the social habitat to combat inequality? If architecture is an art that generates spaces for better living, architects have the responsibility to understand and respect the territory and the people, to propose spaces that represent the culture and spirit of each place.However, in cities we live between physical walls that highlight inequalities and make visible the fear we have of others. In the peripheral areas and, even more, in the rural areas of the country, we contribute a system than abandon the most vulnerable communities. Faced with this scenario, we believe that the first wall we have to tear down is a wall in our minds, and this is only possible through equal access to education. For this reason, we are interested in educational architecture projects: the school, the first place after the home, where children can develop by learning in society.